2014
DOI: 10.1002/2013gl059169
|View full text |Cite
|
Sign up to set email alerts
|

Triggering and runaway processes of catastrophic Tsaoling landslide induced by the 1999 Taiwan Chi-Chi earthquake, as revealed by high-velocity friction experiments

Abstract: Pliocene sedimentary rocks of about 130 Mm 3 in volume slid along bedding planes dipping by 14°, with an average speed of about 35 m/s, during the Tsaoling landslide. We conducted friction experiments to reproduce the initiation processes of this landslide, by idealizing landslide movements during the earthquake as accelerating/decelerating motion. Experiments were done on shale from the field, at 3 MPa normal stress corresponding to the overburden pressure. Results indicate that the accelerating/decelerating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 20 publications
(42 reference statements)
2
32
0
Order By: Relevance
“…As mentioned previously, the friction coefficient decreased from a peak value to a steady-state value with increasing displacement in the slip-weakening regime. The steady-state friction coefficients (μ ss ; red circles with crosses) decreased from approximately 0.27 to 0.05 with increasing velocity (Figure 8), which has been observed in numerous studies of high-velocity rotary shear tests (Miyamoto et al, 2009;Togo et al, 2014). The slipweakening distances (D c ) for our data range from 2.94 to 8.55 m with an average value of 4.90 m (Table 1).…”
Section: Experimental Results On Bedding-parallel Fault Gougesupporting
confidence: 68%
See 4 more Smart Citations
“…As mentioned previously, the friction coefficient decreased from a peak value to a steady-state value with increasing displacement in the slip-weakening regime. The steady-state friction coefficients (μ ss ; red circles with crosses) decreased from approximately 0.27 to 0.05 with increasing velocity (Figure 8), which has been observed in numerous studies of high-velocity rotary shear tests (Miyamoto et al, 2009;Togo et al, 2014). The slipweakening distances (D c ) for our data range from 2.94 to 8.55 m with an average value of 4.90 m (Table 1).…”
Section: Experimental Results On Bedding-parallel Fault Gougesupporting
confidence: 68%
“…Continuous U layers are absent when the shear velocity was less than 0.22 m/s (slip-strengthening regime). The U layer can be observed at a slip velocity of 0.1 m/s (Figure 13a Two datasets of rotary shear tests using dry and wet samples from the Tsaoling landslide site have been reported (Miyamoto et al, 2009;Togo et al, 2014). Togo et al (2014) documented the friction coefficients of dry shale powders of samples from the lower Cholan Formation near the slide plane (squares in Figure 14), and Miyamoto et al (2009) reported friction coefficients of dry bedding-parallel fault gouges (triangles in Figure 14).…”
Section: Microstructural Observationsmentioning
confidence: 98%
See 3 more Smart Citations